Black Sea Container Market and Georgia’s Positioning - Irakli Danelia (European Scientific Journal, ESJ, 2018)
Due to the strategically important geographical location, Black Sea region has a key transit function throughout between Europe and Asia. Georgia, which is a part of Black sea area, has a vital transit function for Caucasus Region, as well as for whole New Silk Road area. Nevertheless, still there is no evidence what kind of role and place Georgia has in The Black Sea container market. As the country has ambition to be transit hub for containerizes cargo flows between west and east and is actively involved in the process of formation “One Belt One Road” project, it is very important to identify Country’s current circumstances, capacities and future potential. Because of this, the purpose of the study is to investigate cargo flows and opportunities of the Black Sea container market, level of competitiveness in the area and define Georgia’s positioning in the regional Container market.